2016
DOI: 10.1093/carcin/bgw032
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune signaling through differential RIPK1 expression promote tumor progression in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a devastating disease for which new treatments, such as immunotherapy are needed. Synthetic double-stranded RNAs, which activate toll-like receptor 3 (TLR3), have been used as potent adjuvants in cancer immunotherapy by triggering a proapoptotic response in cancer cells. A better understanding of the mechanism of TLR3-mediated apoptosis and its potential involvement in controlling tumor metastasis could lead to improvements in current treatment. Using paired, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 24 publications
1
70
0
Order By: Relevance
“…A reduced expression of key molecules in the necroptotic pathway has been observed in different cancer cell lines, suggesting that these cells may evade necroptosis to survive [6]. As a consequence, a lower expression of necroptosis regulators seems to correlate with a worse prognosis in several types of carcinomas (i.e., breast, colorectal, gastric, and ovarian cancer, and head and neck and cervical squamous cell carcinoma), in acute myeloid leukemia, and in melanoma [30,[42][43][44][45][46][47][48]. However, the expression of RIPK1, RIPK3, and MLKL has been found to be upregulated in some cancers (i.e., glioblastoma, pancreatic, lung, and esophageal cancer), in which a high activation of the necroptotic cascade seems to be correlated with a poorer prognosis in different studies [6,36,41,[49][50][51][52][53].…”
Section: Pro-tumoral Effects Anti-tumoral Effectsmentioning
confidence: 99%
“…A reduced expression of key molecules in the necroptotic pathway has been observed in different cancer cell lines, suggesting that these cells may evade necroptosis to survive [6]. As a consequence, a lower expression of necroptosis regulators seems to correlate with a worse prognosis in several types of carcinomas (i.e., breast, colorectal, gastric, and ovarian cancer, and head and neck and cervical squamous cell carcinoma), in acute myeloid leukemia, and in melanoma [30,[42][43][44][45][46][47][48]. However, the expression of RIPK1, RIPK3, and MLKL has been found to be upregulated in some cancers (i.e., glioblastoma, pancreatic, lung, and esophageal cancer), in which a high activation of the necroptotic cascade seems to be correlated with a poorer prognosis in different studies [6,36,41,[49][50][51][52][53].…”
Section: Pro-tumoral Effects Anti-tumoral Effectsmentioning
confidence: 99%
“…For example, the analysis of RIPK3 expression in 74 primary CRC tumors treated with first-line 5-fluorouracil (5-FU) chemotherapy revealed that high expression levels of RIPK3 correlated with a significantly longer overall survival and lower risk of disease progression in CRC patients [208]. Consistent with this, low expression of RIPK1 was correlated with, higher tumor progression in head and neck squamous cell carcinoma (HNSCC) patients [209] and worse prognosis in human hepatocellular carcinoma (HCC) patients [210]. In contrast to this, higher expression of RIPK1 was also linked to a worse prognosis and higher metastasis rate in melanoma, potentially due to NF-κB-dependent stimulation of cancer cell proliferation [211].…”
Section: Sp1mentioning
confidence: 84%
“…Head and neck cancer (HCC) Worse prognosis [209] Head and neck cancer (HCC) Worse prognosis [210] High expression Breast cancer Promotes metastasis [226] Glioblastoma Worse prognosis [227] MLKL expression…”
Section: Low Expressionmentioning
confidence: 99%
“…The receptor-interacting protein kinase 1 (RIPK1) and 3 (RIPK3), as well as their target, the mixed lineage kinase domain-like protein (MLKL), are required to initiate necroptosis [ 5 , 6 , 7 ]. Necroptosis is associated with various human diseases including ischemic reperfusion injury, inflammatory, neurodegenerative, infectious, autoimmune diseases and cancer [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Recently, necroptosis has been also involved in mediating organ rejection in cardiac and renal allografts [ 8 , 12 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%